Pengelompokan Penyebaran Produk Yamaha Menggunakan Metode K-Means Clustering Sun Berlian Motor Di Jl. SM Raja Bakaran Batu - Tanjung, Riska Wulandari; Suryadi, Sudi; Ritonga, Wahyu Azhar (LPPM Universitas Al Washliyah Labuhanbatu, 2024)
Design of the K-Means Method for Grouping the Distribution of Yamaha Sun Berlian Motor Products on Jl. SM Raja Bakaran Batu based on motorbike type and color. Research data can be grouped based on the type and color of motorbike. Using the K-Means Clustering Method. The complete results of the K-Means calculation process to determine the type and color of the Yamaha motorbike sun diamond are grouped into 4 clusters according to the type and color of the motorbike. Where the number of motorbikes in cluster 1 according to type and color is 51, cluster 2 is 29, cluster 3 is 23 and cluster 4 is 5.